VOLCANO - ESTRATIGRAFÍA ASOCIADA AL CAMPO DE DOMOS DE CAÑAS DULCES, GUANACASTE, COSTA RICA - Zamora, Natalia (2011)
A geovolcanic mapping and a stratigraphic sequence interpretation of the volcanic products relatedto a calderic complex, located at the SW of the Rincón de la Vieja volcano, are presented. Sixteen main litostratigraphic units were recognized with a Paleocene to Miocene basement of hydrotermalized sedimentary rocks.During the Pliocene, the Alcántaro volcanic system emerged; small calderas (Guachipelín) and ignimbrite depositswere formed. An extended fluviolacustrine sequence (> 96 km2) with a strong volcanic influence and diatomitedeposits represent the sediments of an ancient lake originated within the Alcántaro-Guachipelín caldera. Four phases of evolution of the volcanic and lacustrine deposits can be distinguished: 1) Formation of the caldera and theAlcántaro ignimbrite deposit facies, 2) migration of the activity to the SE, 3) formation of the Guachipelín caldera, and 4) most of the caldera was reactivated and the pericalderic and intracalderic dacite-rhyolitic domes wereformed. Later on, the present Rincón de la Vieja volcano was originated. A series of debris flows and debris avalanches coming from the Rincón de la Vieja and Cacao volcanoes covered the NW part of the study area. About 3500 years ago a subplinian layer, erupted from the Rincón de la Vieja volcano, covered the topography.